2597. Dolichos biflorus Agglutinin Binds to Pneumococcal Teichoic Acid and Lipoteichoic Acid - Zhou, Meng-Lan (Open Forum Infect Dis, 2019)
BACKGROUND: Dolichos biflorus agglutinin (DBA) is a lectin with a binding specificity toward α-linked N-acetylgalactosamine (α-GalNAc). While DBA is known to bind some, but not all, pneumococci, its target molecule has not been identified. Pneumococcus teichoic acid (TA) and lipoteichoic acid (LTA) have repeating units with α-GalNAc-(1→3)β-GalNAc decorated with phosphorylcholine (PC) at the O-6 positions. Two PC transferases, LicD1 and LicD2, mediate the attachment of PC to GalNAc residues while phosphorylcholine esterase (Pce) removes PCs attached to the terminal GalNAcs. We examined if DBA binds to the terminal α-GalNAc-(1→3)β-GalNAc created by Pce. METHODS: Fifteen pneumococcus strains expressing 14 different serotypes, including one non-encapsulated strain (R36A), were studied with flow cytometry (FC) and confocal fluorescence microscopy (CFM) for DBA binding. Pce enzyme activity was detected with a colorimetric assay using p-nitrophenyl-phosphorylcholine as the substrate. Mutant strains with pce knocked-out were constructed in R36A and D39 by replacing pce with Janus cassette. Both licD genes were sequenced for some of the strains. RESULTS: Ten of the 15 strains had Pce activity and all of them bound DBA (Table 1). When the pce gene was inactivated in two normally Pce-positive strains (R36A(△pce) and D39(△pce)), the strains did not show DBA binding by CFM (Figure 1). Thus, expression of Pce appears to be sufficient for expressing the DBA antigen. Of the five strains that had no Pce activity, two bound DBA. Sequencing of the licD genes in these two strains with positive DBA binding and negative Pce activity revealed one SNP in licD1 and four SNPs in licD2, resulting in a single amino acid difference each for LicD1 and LicD2, compared with R36A and D39. CONCLUSION: DBA can bind to the terminal α-GalNAc-(1→3)β-GalNAc of pneumococcal TA and LTA, which is created by Pce. DBA binding is independent of capsule type. The unexpected binding of DBA to the two Pce-negative strains suggests that there is a Pce-independent mechanism for generating the target for DBA binding. Since LicD1 and LicD2 are involved in attaching PC to α-GalNAc-(1→3)β-GalNAc, we are now investigating their role in creating DBA targets independent of Pce. [Image: see text] [Image: see text] DISCLOSURES: All authors: No reported disclosures.